Internalization of Islamic Values ​​in the Mapag Bridal Tradition of the Sundanese Community in Banjar Kerta Rahayu Village, Central Lampung - Kharisma Selviana; Hasyim As’ari; Lutfi Fadilah (Journal of Research in Islamic Education, 2026)
The Mapag Panganten tradition is a cultural heritage of the Sundanese people that is still preserved in Banjar Kerta Rahayu Village, Central Lampung. This tradition not only functions as a series of welcoming ceremonies for the bride and groom, but also contains spiritual, social, and religious values ​​that reflect Islamic teachings. This study aims to analyze the process of internalization of Islamic values ​​in the Mapag Panganten tradition and identify the forms of Islamic values ​​contained therein. This study uses a qualitative approach with a field study method. Data were obtained through observation, in-depth interviews with traditional leaders, religious leaders, and the community, as well as documentation of Mapag Panganten traditional activities. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Mapag Panganten tradition contains Islamic values ​​such as the values ​​of monotheism, manners and morals, prayer and trust, Islamic brotherhood, and gratitude to Allah SWT. The process of internalization of values ​​occurs through ritual symbols, prayers, advice from traditional and religious leaders, and community involvement in each series of events. This tradition serves as an effective means of culturally instilling Islamic teachings in the community, especially the younger generation, thereby maintaining a balance between religious values ​​and local culture. Mapag Panganten serves not only as a cultural tradition but also as a medium for educating Islamic values ​​in the social life of the Banjar Kerta Rahayu Village community.